2021
DOI: 10.1021/acs.estlett.1c00172
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Reproducible Characterization of the Wavelength Dependence of Aquatic Photochemical Reactions Using Light-Emitting Diodes

Abstract: Arguably, the largest knowledge gap in the aquatic photochemistry discipline is the wavelength dependence of sunlight-driven reaction rates in surface waters. Here, we introduce a new light-emitting diode (LED)-based approach to directly quantify the wavelength dependence of aquatic photochemical reaction rates. The LEDs generate narrowbanded, spatially uniform light at five wavelengths (275, 309, 348, 369, and 406 nm), with irradiances that are stable and easily adjusted to desired levels. Strong agreement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Photo-dissolution AQYs were experimentally determined as a function of wavelength and photon dose by irradiating uniform, 200-μm-thick oil films under narrow (~20 nm) wavebands of UV and visible light provided by custom-built LED-based reactors that allowed for easy control over irradiant output (Fig. 1) ( 24 ). Oil films were irradiated at a total of eight wavebands from 278 to 629 nm and four photon doses corresponding to environmental sunlight exposure times on the scale of days (for visible light) to years (for short-wavelength UV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo-dissolution AQYs were experimentally determined as a function of wavelength and photon dose by irradiating uniform, 200-μm-thick oil films under narrow (~20 nm) wavebands of UV and visible light provided by custom-built LED-based reactors that allowed for easy control over irradiant output (Fig. 1) ( 24 ). Oil films were irradiated at a total of eight wavebands from 278 to 629 nm and four photon doses corresponding to environmental sunlight exposure times on the scale of days (for visible light) to years (for short-wavelength UV).…”
Section: Resultsmentioning
confidence: 99%
“…Using a custom-built light-emitting diode (LED) reactor system (Fig. 1) ( 24 ), we found that oil photo-dissolution AQYs decrease exponentially with increasing wavelength, reactivity extends deep into the visible light region, and AQYs decrease with increasing photon dose. The sensitivity analysis revealed that rates were most sensitive to oil slick thickness, season/latitude, and wavelength and less sensitive to photon dose.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ward et al reported the application of narrow-banded light-emitting diode (LED) lights for measuring the QY spectrum of photochemical oxygen consumption by CDOM. 16 The LED light-based photolysis system demonstrates high sample throughput, low cost, and simple instrument setups, shedding light on assessments of wavelength-dependent aquatic photochemical processes. The goal of this study was to assess the wavelength-dependent QY of PPRI productions using a custom-made LED setup.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yet the applications of theses traditional irradiation setups for studying aquatic photochemistry are limited either by the high equipment cost of the laser or by the low tunability of light bandwidth and irradiance with optical filters. Recently, Ward et al reported the application of narrow-banded light-emitting diode (LED) lights for measuring the QY spectrum of photochemical oxygen consumption by CDOM . The LED light-based photolysis system demonstrates high sample throughput, low cost, and simple instrument setups, shedding light on assessments of wavelength-dependent aquatic photochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 : 1 assumption would imply a consumption of only ~ 30 μ M O 2 in 48 h, and it is unknown whether this ~ 15% loss in O 2 is enough to impact DIC photoproduction rates. Although photochemical AQY spectra for photochemical O 2 consumption have been determined (Andrews et al 2000; Cory et al 2014; Ward et al 2021), work is needed to determine how AQY spectra (for both O 2 loss and DIC production) vary at various O 2 concentrations to predict how these processes may change over the course of exposure. This uncertainty again demonstrates that it is important to aim for the shortest irradiation time possible that still allows for reliable DIC determination, and that the development of new methods, where DIC photoproduction can be determined over very short time scales, thus minimizing photochemical O 2 loss, will also help in this regard (Bowen et al 2020; Ward et al 2021).…”
Section: Discussionmentioning
confidence: 99%